Lects in Helsinki Finnish - a probabilistic component modeling approach. (March 2021) - Kuparinen, Olli; Peltonen, Jaakko; Mustanoja, Liisa; Leino, Unni; Santaharju, Jenni
Abstract: This article examines Finnish lects spoken in Helsinki from the 1970s to the 2010s with a probabilistic model called Latent Dirichlet Allocation. The model searches for underlying components based on the linguistic features used in the interviews. Several coherent lects were discovered as components in the data, which counters the results of previous studies that report only weak covariation between features that are assumed to be present in the same lect. The speakers, however, are not categorical in their linguistic behavior and tend to use more than one lect in their speech. This implies that the lects should not be considered in parallel with seemingly uniform linguistic systems such as languages, but as partial systems that constitute a network.